Surviving in a Warmer Marine World: A Study on the Impact of Thermal Effluent on Posidonia oceanica Meadows and Associated Fish Assemblages in the Maltese Islands - Alessio Marrone; Alessandro Rinaldi; Valeria Montalto; Adam Gauci; Francesca Ape; Henri Ringeard; Marco Spoto; Marco Martinez; Emanuela Claudia La Marca; Simone Mirto; Alan Deidun (Journal of Marine Science and Engineering)
Ocean warming poses significant threats to coastal ecosystems. This study investigates the impact of thermal effluents from power plants, as proxies for climate-driven temperatures increase, on Posidonia oceanica meadows and associated fish communities. Using a gradient-based approach, we analyzed environmental variables, seagrass indicators, fish assemblages, and functional group (FG) dynamics across a thermal gradient extending from the effluent outfall itself. Results indicate that temperature is the dominant factor influencing P. oceanica, with reduced leaf length, shoot density, and rhizome weight characterizing samples closest to the effluent. Despite compensatory mechanisms, the overall photosynthetic biomass and resilience declined under thermal stress. Fish assemblages exhibited reduced species richness and biodiversity close to the thermal effluent, with opportunistic and thermophilic species dominating. An FG analysis revealed disrupted seasonal patterns, shifts in trophic dynamics, and functional compensation among species, highlighting potential ecological imbalances. Notably, transient predators thrived near the effluent, while more sedentary and temperate species were displaced. These findings underscore the cascading effects of rising temperatures on coastal habitats such as P. oceanica meadows and their associated communities, emphasizing the urgency for conservation measures. By identifying critical thresholds and adaptive responses, this study contributes valuable insights into the consequences of localized impacts of thermal stress on coastal biodiversity and ecosystem services.